Zonasi Risiko Multibahaya di Wilayah Pesisir Pantai Kota Surabaya Berdasarkan Perspektif Perubahan Penggunaan Lahan - , Annisaa Hamidah I. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Surabaya City as one of the biggest city in Indonesia regarding its function as service central and warehousing business. The objective of this study is to obtain prediction on spatial distribution of multihazard risk in coastal area in Surabaya based on the perspective of land use. The knowledge regarding the prediction on spatial distribution of multihazard risk is a nonstructural measure which is used as basic information and input in the planning and management of Surabaya City. The multihazard risk is calculated according to the hazard of land subsidence, tidal inundation and land use vulnerability in 2013 and 2030. The modeling of tidal inundation is done by the analysis of conditional model in ArcGIS and Ilwis with the input of the tendency value of the increasing water level and DEM map which acomodate the land subsidence as result of the modeling of land subsidence. Land use is modeled using cellular automata to evaluate the prediction on the land use condition in 2030. The multihazard risk is analyzed using raster calculator in ArcGIS with the input of the result of multihazard and land use change modeling. Result indicates that the inundation level and land use inflicted the different level of risk in each area. Asemrowo sub-district is the area with the highest percentage of risk value. In 2013, it is predicted to have major expansion on the distribution of multihazard risk in the area to 6.24 % starting from 2013. Keyword: multihazard, risk, vulnerability, land subsidence, tidal inundation, land use change